The outcomes of root canal treatment undertaken by dental students in Kulliyyah of Dentistry, IIUM: tooth survival - Mustaffa, Musliana; Mat Daud, Muhamad Sharifuddin; Mohd Ibrahim, Mohamad Shafiq (Ectodermal Dysplasia Group-Turkey, 2021)
It is not known whether or not root canal treatment provided by undergraduate dental students in the Kulliyyah of Dentistry (KOD), International Islamic University Malaysia (IIUM) is successful; therefore, the need to investigate the outcome of treatment is indispensable. This study was conducted at the KOD, IIUM from 11th July 2018 until 12th June 2019. Follow up visits were conducted at least 6 months after the completion of root canal treatment. A total of 175 root canal treated teeth from 143 patients aged between 17 and 71 years old were still present during the follow up visits. Information on the extraction of root canal treated teeth, including reasons for extraction was obtained from the patients or patient’s records. Treatment was considered failed when the tooth was extracted due to fracture or persistent intraradicular infection. The results show that survival rate of root canal treated teeth was 98.9% over an observation period of at least 42 months. Two root canal treated teeth were extracted due to tooth fracture. Root canal treatment provided by undergraduate dental students in the Kulliyyah of Dentistry was effective, with minimal percentage of failure.